Optimization of the Fermentation Media and Parameters for the Bio-control Potential of Trichoderma longibrachiatum T6 Against Nematodes - Zhang, Shuwu; Gan, Yantai; Liu, Jia; Zhou, Jingjiang; Xu, Bingliang (Frontiers in Microbiology, 2020)
The cereal cyst nematode Heterodera avenae is one of important soil-borne pathogens of cereal crops and causes high yield losses worldwide. Trichoderma spp. formulations are applied as commercial bio-control agents against soil-borne plant pathogens such as H. avenae. However, the relationship between T. longibrachiatum fermentation parameters and its bio-control potential against H. avenae has not exclusively established. In the present study, the effect of ten different fermentation media and conditions on the nematicidal activity of T. longibrachiatum T6 (T6) was evaluated with single-factor method and Plackett-Burman design, and the interaction between different fermentation parameters was investigated by Box-Behnken design. The variables for enhancing the nematicidal activity of T6 culture filtrates was explored and optimized using response surface methodology (RSM). The Minor Medium (MM) plus wheat bran-2 medium was found to be the most effective fermentation medium for T6 culture filtrates against the second stage juveniles (J2s) of H. avenae. The maximum mortality of the J2s was obtained using the T6 culture filtrates under the fermentation condition: initial pH 6, 28oC culture temperature, 180 rpm rotating speed, 60 ml of fermentation media, 7 days of incubation time and 1 ml of inoculation volumes. Among these parameters, the initial pH, inoculation volume and incubation day were identified as the most significant parameters and critical independent variables for enhancing the nematicidal activity of the T6 culture filtrates. After further optimizations based on statistical predictions, the highest nematicidal activity (92.42%) was obtained with the T6 culture filtrates fermented under initial pH of 6.06, inoculation volume of 1.62 ml and incubation time of 7.15 days. The nematicidal activity was increased approximately by as high as 1.07% compared with that before optimization. Bio-control efficacy of T6 culture filtrates was 83.88% at the seventieth day after wheat seeds sowing in greenhouse experiments. The results from the validation experiments agreed with the model predictions. Our study has improved the bio-control potential of Trichoderma spp. against the plant-parasitic nematodes H. avenae, and provided a cost-efficient bio-resource in the future development of novel bio-control agents.